2020
DOI: 10.1097/mat.0000000000000955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heart Rate Reserve on Exercise Capacity in Patients Treated with a Continuous Left Ventricular Assist Device

Abstract: We hypothesized that an inadequate increase in heart rate (HR) during exercise was associated with low peak oxygen uptake (VO2 peak) seen in left ventricular assist device (LVAD) recipients and aimed to analyze the potential relation between HR and VO2 peak and use of drugs with negative chronotropic effect. Sixty-eight LVAD recipients (44 Heartmate 2 and 24 HeartWare Ventricular Assist Device) with support duration >1 month and a VO2 peak were included from two centers. Patients were 57 ± 13 years at time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
3
7
0
Order By: Relevance
“…Postimplantation mean pVO 2 values ( Figure 2B ) vary from 8.8 to 21.4 ml/kg/min (mean pVO 2 weighted for population size 13.2 ml/kg/min), showing that pVO 2 generally remains reduced after implantation at, on average, 48% of the expected value for age and sex. [ 12 16 , 21 23 , 25 29 , 31 37 , 39 42 , 44 47 , 61 63 ] A considerable proportion of the variance of postimplantation pVO 2 between published studies can be attributed to differences in the mean age of included patients. [ 11 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Postimplantation mean pVO 2 values ( Figure 2B ) vary from 8.8 to 21.4 ml/kg/min (mean pVO 2 weighted for population size 13.2 ml/kg/min), showing that pVO 2 generally remains reduced after implantation at, on average, 48% of the expected value for age and sex. [ 12 16 , 21 23 , 25 29 , 31 37 , 39 42 , 44 47 , 61 63 ] A considerable proportion of the variance of postimplantation pVO 2 between published studies can be attributed to differences in the mean age of included patients. [ 11 ]…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have documented the negative effects of chronotropic incompetence on exercise capacity in LVAD recipients. [ 12 , 21 , 27 , 38 , 46 ] Depending on the definition of chronotropic incompetence, it has been reported in approximately half of all examined LVAD recipients. Chronotropic incompetence may represent a somewhat clinically modifiable factor, because many LVAD recipients receive beta-blockers, digoxin or amiodarone and are equipped with pacing devices that could be programmed to improve chronotropic competence.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the close relationship between heart rate and oxygen consumption, especially when its intensity is between 50 and 90% of functional capacity (VO 2 max). Heart Rate Reserve (HRR) is the difference between a person's maximum Heart Rate (HRmax) (estimating as age -220) and resting Heart Rate (HRrest) [14]. The most accurate way to regulate the intensity of aerobic exercise using this method is to determine a specific heart rate with a VO 2 max or heart rate associated with lactate threshold.…”
Section: Heart Rate a Variable For Controlling The Exercise Intensitymentioning
confidence: 99%
“…21,25 The role of heart rate is under investigation, 26,27 since, although it seems not to affect LVAD flows, 25 a recent study investigating 68 LVAD recipients (44 HeartMate II and 24 HeartWare HVAD) reported chronotropic incompetence in 44% of the patients which was clearly associated with a lower peakVO 2 , while this relation was not affected by beta-blocker therapy. 28…”
Section: Introductionmentioning
confidence: 99%